1998
DOI: 10.1021/jf970812n
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Products Formed from Glucosamine in Water

Abstract: An aqueous solution of glucosamine hydrochloride was heated to 150 °C for 5 min under different pH conditions. The reaction product mixture obtained was analyzed by GC/MS. It was found that the major products formed were furfurals, especially at pH = 4 and 7. At pH = 8.5, additional flavor components were generated, including pyrazines, 3-hydroxypyridines, pyrrole-2-carboxaldehyde, furans, acetol, and several other compounds. Of the components identified, it is worthwhile to note the formation of pyrazine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 1 publication
2
23
0
Order By: Relevance
“…[36][37][38] In this way, several interaction products are formed that are mainly related to substituted pyridines andp yrroles. [42][43][44][45] These compounds may also be generated through the condensation of aldehydes, ketones or a,bunsaturated carbonylic compounds with ammonia. [39][40][41] Pyridines are likely formed through aM aillard-type reaction that involves acarbonyl group of afurfural derivatives and ammonia (derived from carbohydratesa nd from protein degradation, respectively) according to the proposed mechanisms shown in Scheme 2.…”
Section: Gc-ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38] In this way, several interaction products are formed that are mainly related to substituted pyridines andp yrroles. [42][43][44][45] These compounds may also be generated through the condensation of aldehydes, ketones or a,bunsaturated carbonylic compounds with ammonia. [39][40][41] Pyridines are likely formed through aM aillard-type reaction that involves acarbonyl group of afurfural derivatives and ammonia (derived from carbohydratesa nd from protein degradation, respectively) according to the proposed mechanisms shown in Scheme 2.…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…[39][40][41] Pyridines are likely formed through aM aillard-type reaction that involves acarbonyl group of afurfural derivatives and ammonia (derived from carbohydratesa nd from protein degradation, respectively) according to the proposed mechanisms shown in Scheme 2. [42][43][44][45] These compounds may also be generated through the condensation of aldehydes, ketones or a,bunsaturated carbonylic compounds with ammonia. [46] Pyrroles can be formed through three major pathways: (i)Strecker degradation between an amino acid and 3-deoxyhexosone followed by dehydration and ring closure; [47] (ii)conjugation of furan derivatives( with ac arbonyl function in the 2position) with amines or amino acids (Scheme 2); [48] (iii)Knorr condensation of a-aminocarbonyls with ketoneso ra ldehydes.…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Therefore, D‐glucosamine and its salts are employed in dietary supplement products, which have demonstrated positive effects on the treatment of osteoarthritis, knee, and back pain . In the context of sustainable chemistry, D‐glucosamine was recently proposed as a renewable precursor for the preparation of valuable specialty chemicals, such as 5‐(hydroxymethyl)furfural and other furfural derivatives …”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43] In the context of sustainable chemistry, D-glucosamine was recently proposed as a renewable precursor for the preparation of valuable specialty chemicals, such as 5-(hydroxymethyl)furfural and other furfural derivatives. [17,44,45] The use of co-solvents during the acidic hydrolysis has been proposed as a strategy to decrease the concentration of corrosive acids used during chitin hydrolysis. Recently, Zhang and Yan demonstrated that using diethylene glycol diethyl ether as co-solvent provided glucosamine in 80% yield of from pure chitin using low concentration of sulfuric acid at 175 °C, for 1 h. [46] Having in mind the importance of obtaining D-glucosamine from renewable sources, this work describes the isolation of pure D-glucosamine from three biomass residues: shrimp shells, cicada sloughs, and cockroaches, using a general protocol that works for all chitin sources tested.…”
Section: Introductionmentioning
confidence: 99%
“…Davidek et al 15 studied the effects of phosphate ions on the degradation products of 1-L-glycine-1-deoxy-Dfructose, and the results showed that the addition of phosphate ions could accelerate the degradation processes. Shu et al 16 reported that at a pH of 8.5, the major products formed from the degradation of glucosamine were pyrazine and methylpyrazine. Hofmann et al 17 reported that the formation of phenylacetaldehyde was favored during the degradation of 1-Lphenylalanine-1-deoxy-D-fructose catalyzed by ambient oxygen.…”
Section: Introductionmentioning
confidence: 99%